Occurrence of COVID-19 in cystic fibrosis patients: a review - Abolhasani, Fatemeh Sadat; Moein, Masood; Rezaie, Niloofar; Sheikhimehrabadi, Parimah; Shafiei, Morvarid; Afkhami, Hamed; Modaresi, Mohammadreza (Frontiers in Microbiology, 2024)
Cystic fibrosis (CF) is a genetic ailment caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. This autosomal recessive disorder is characterized by diverse pathobiological abnormalities, such as the disorder of CFTR channels in mucosal surfaces, caused by inadequate clearance of mucus and sputum, in addition to the malfunctioning of mucous organs. However, the primary motive of mortality in CF patients is pulmonary failure, which is attributed to the colonization of opportunistic microorganisms, formation of resistant biofilms, and a subsequent decline in lung characteristics. In December 2019, the World Health Organization (WHO) declared the outbreak of the radical coronavirus disease 2019 (COVID-19) as a worldwide public health crisis, which unexpectedly spread not only within China but also globally. Given that the respiration system is the primary target of the COVID-19 virus, it is crucial to investigate the impact of COVID-19 on the pathogenesis and mortality of CF patients, mainly in the context of acute respiratory distress syndrome (ARDS). Therefore, the goal of this review is to comprehensively review the present literature on the relationship between cystic fibrosis, COVID-19 contamination, and development of ARDS. Several investigations performed during the early stages of the virus outbreak have discovered unexpected findings regarding the occurrence and effectiveness of COVID-19 in individuals with CF. Contrary to initial expectancies, the rate of infection and the effectiveness of the virus in CF patients are lower than those in the overall population. This finding may be attributed to different factors, including the presence of thick mucus, social avoidance, using remedies that include azithromycin, the fairly younger age of CF patients, decreased presence of ACE-2 receptors, and the effect of CFTR channel disorder on the replication cycle and infectivity of the virus. However, it is important to notice that certain situations, which include undergoing a transplant, can also doubtlessly boost the susceptibility of CF patients to COVID-19. Furthermore, with an increase in age in CF patients, it is vital to take into account the prevalence of the SARS-CoV-2 virus in this population. Therefore, ordinary surveillance of CF patients is vital to evaluate and save the population from the capability of transmission of the virus given the various factors that contribute to the spread of the SARS-CoV-2 outbreak in this precise organization.